The Validity of the Human Circulatory System Concepts Handout at Class XI IPA SMAN 6 Banjarmasin - Farida Rahmi; Noorhidayati Noorhidayati; Maulana Khalid Riefani (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2020)
The use of good and appropriate teaching materials during the teaching and learning process can make learning more meaningful, namely creating an atmosphere of active learning for students, so that students can achieve the competencies expected by understanding the concepts of learning. The concept of the human circulatory system is a Biological concept that is relatively difficult to understand, so research and development of teaching materials are carried out in the form of handouts. This research and development aim to describe the validity of the concept handout of the human circulatory system of class XI IPA SMAN 6 Banjarmasin. This research is a type of research and development with a 4D development model. This research is limited only to the Develop stage. The results of the research and development of the concept handout of the human circulatory system of class XI IPA SMAN 6 Banjarmasin are classified as very valid with a validity value of 90%.AbstrakPenggunaan bahan ajar yang baik dan tepat selama proses belajar mengajar dapat membuat pembelajaran menjadi lebih bermakna yaitu menciptakan suasana belajar yang aktif bagi peserta didik, sehingga peserta didik mampu mencapai kompetensi yang diharapkan dengan memahami konsep pembelajaran. Konsep sistem peredaran darah manusia merupakan konsep Biologi yang relatif sulit dipahami, sehingga dilakukan penelitian dan pengembangan bahan ajar berupa handout. Penelitian dan pengembangan ini bertujuan untuk mendeskripsikan validitas handout konsep sistem peredaran darah manusia kelas XI IPA SMAN 6 Banjarmasin. Penelitian ini adalah jenis penelitian dan pengembangan dengan model pengembangan 4D. Penelitian ini dibatasi hanya sampai pada tahap Develop (Pengembangan). Hasil penelitian dan pengembangan handout konsep sistem peredaran darah manusia kelas XI IPA SMAN 6 Banjarmasin tergolong sangat valid dengan nilai validitas yaitu 90%.